Kebiasaan Konsumsi Makanan Siap Saji dan Status Obesitas Pada Anak Sekolah Dasar - Mohamad Renaldiyanto Lowanga; Salman Salman; Anna Y Pomalingo; Indra Domili; Misnati Misnati (JOURNAL OF NONCOMMUNICABLE DISEASES, 2021)
Obesity that occurs in school children is caused by wrong eating patterns, namely children like snacks that are high in fat and high in sugar. In addition, excess intake of energy and fat accompanied by a lack of activity also affects the incidence of obesity. This study aims to determine the description of fast food consumption habits and obesity status in elementary school children in Tanggilingo Village, Kabila District, Bone Bolango Regency. This research method uses a descriptive survey. The population is all students in Tanggilingo Village, Kabila District, Bone Bolango Regency. Independent research variables, namely the habit of consuming fast food and obesity status in elementary school children. The results of the study: showed the habit of consuming fast food for school children in the frequent category of 25 people (83.3%) and the less category as many as 5 people (16.7%). Obese nutritional status of school children who are obese (3.3%) and non-obese (96.7%). The conclusion of the study that most school children have a habit of frequently consuming fast food and obesity status is 1 person (3.3%).